Deploying wireless sensor networks : theory and practice - Senouci, Mustapha Reda (Sensor Networks Set., 2016)
Wireless Sensor Networks: Theory and Practice for Deployment addresses WSNs deployment, a mandatory and critical step in the process of developing WSNs solutions for real-life applications. The authors address simple approaches to deploy static WSNs, then exploring moreiAsophisticated approaches to deploy mobile WSNs. Featuring detailed investigations of deployment-related issues such as deployment cost, coverage, connectivity, sensors reliability, and harsh deployment environments, this book will equip you with the basics and an advanced view of both the theoretical and practical aspects, along with knowledge of theiAguidelines for WSNs deployment.